Environmental test of improved in vitro potato varieties in the conditions of Central Yakutia - V. G. Darkhanova; N. S. Stroeva; I. V. Voronov; G. V. Filippova (Аграрная наука Евро-Северо-Востока, 2021)
Ecological tests of improved in vitro plants - potato regenerants of promising and zoned in Central Yakutia varieties have been carried out on cryogenic flood plain fibrous saline soils. To conduct a field experiment, clones adapted to the soil (2019) and their tuberous offspring (2020) were planted at the end of May. It was revealed that the most resistant to open ground conditions were regenerants of the Krasavchik variety (survival rate - 28.0 %); the least adapted variety was Vasilek (1.0 %). It has been established that among improved zoned varieties the most tolerant to arid conditions of vegetation (hydrothermal coefficient 0.4) and more productive (average tuber weight 213.9 g) was the Adretta variety. High index of tuber safety (100.0±5.0 %) was observed in Adretta variety (37 pcs.) and promising varieties Riviera (18 pcs.), Triumf (40 pcs.) and Rodrigo variety (16 pcs., 94.1±4.7 %). Zoned variety Vasilek (12 pcs., 80.0±4.0 %) and promising variety Assol (77.3±3.9 %, 17 pcs.) had no statistical difference in these indexes. The safety of Krasavchik variety tubers was 69.1±4.0 % (241pcs.). Zoned variety Rozard (65 pcs., 55.6±2.8 %) and promising Ilona variety had the same tuber safety. Minimum level of tuber safety was observed in Velina variety (18 pcs., 33.3±1.7 %).